2006
DOI: 10.1590/s0100-879x2006000600013
|View full text |Cite
|
Sign up to set email alerts
|

A pyrazolyl-thiazole derivative causes antinociception in mice

Abstract: The present study investigates the antinociceptive effect of the pyrazolyl-thiazole derivative 2-(5-trichloromethyl-5-hydroxy-3-phenyl-4,5-dihydro-1H-pyrazol-1-yl)-4-(4-bromophenyl)-5-methylthiazole (B50) in mice. Male albino Swiss mice (30-40 g) were used in the acetic acid-induced abdominal writhes and tail-immersion tests. B50 caused dose-dependent antinociception (8, 23 and 80 µmol/kg, sc) in the acetic acid writhing assay (number of writhes: vehicle: 27.69 ± 6.15; B50 (8 µmol/kg): 16.92 ± 3.84; B50 (23 µm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…MPF4 is a novel pyrazole derivative discovered by screening compounds containing a pyrazole scaffold to find new antinociceptive drugs (De Souza et al, 2001;Godoy et al, 2004;Tabarelli et al, 2004;Prokopp et al, 2006;Sauzem et al, 2008). Recently, it was reported that MPF4 presented antinociceptive effects in formalin and hot-plate tests with efficacies similar to dipyrone or morphine (Milano et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…MPF4 is a novel pyrazole derivative discovered by screening compounds containing a pyrazole scaffold to find new antinociceptive drugs (De Souza et al, 2001;Godoy et al, 2004;Tabarelli et al, 2004;Prokopp et al, 2006;Sauzem et al, 2008). Recently, it was reported that MPF4 presented antinociceptive effects in formalin and hot-plate tests with efficacies similar to dipyrone or morphine (Milano et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Many pyrazolylthiazoles have been synthesized using different procedures and showed antinociceptive, anti-inflammatory and antimicrobial activities [2][3][4][5][6][7][8][9][10]. The X-ray crystal structures for related compounds have been published recently [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…7,159.7,152.4,146.0,145.6,133.6,129.8 (2C),129.4,129.2,128.6 (2C),128.3,128.0 (2C),125.9 (2C),111.7,111.4,61.5,14.4;HRMS (ESI) (d,J=7.2 Hz,2H),7.49 (d,J=8.4 Hz,2H),7.43 (d,J=8.4 Hz,2H),4H),6.99 (s,1H),4.47 (q,J=7.2 Hz,2H), 1.44 (t, J=7.2 Hz, 3H); 13 C NMR (100 MHz, CDCl 3 ) δ: 161. 3, 128.0, 125.8 (2C), 121.6, 110.4, 61.3, 14.4, 9.4 2,159.6,152.2,143.6,138.5,136.3,136.1,133.6,132.9,129.4,128.7 (2C),128.2,128.1,127.1,125.7 (2C),122.5,110.0,61.3,14.4,9.2;HRMS (ESI) 3,159.8,152.2,…”
Section: Preparation Of 3 Via Claisen Condensationmentioning
confidence: 99%